The Effectiveness of Web-Based RIASEC-Assisted Career Information Services in Enhancing Students’ Career Self-Efficacy and Career Decision-Making - Rahayu Kuncoro; Dwi Yuwono Puji Sugiharto; Sugiyo Sugiyo (Indonesian Journal of Guidance and Counseling: Theory and Application, 2025)
Career decision-making and career self-efficacy are essential components of students’ readiness to determine their future educational pathways and career directions. However, not all students possess clear career goals or sufficient preparedness, which often leads to difficulties in selecting career options aligned with their personal potential. This study aimed to examine the effectiveness of web-based career information services grounded in the RIASEC model in improving students’ career self-efficacy and career decision-making. A one-group pretest–posttest design was employed.  Purposive sampling was used to select 30 participants who met the predetermined criteria. The participants were then categorized into two analytical groups: a career self-efficacy group and a career decision-making group. Data were analyzed using a paired-samples t-test with SPSS version 23. The results of the analysis (0.00 < 0.05) indicated a significant increase in the mean scores of both career self-efficacy and career decision-making after the implementation of the web-based RIASEC-assisted career information service.  The findings suggest that the intervention was effective in improving both variables. However, the service demonstrated greater effectiveness in enhancing students’ career self-efficacy compared to their career decision-making.